Indonesian EFL Students’ Writing Anxiety: Level Types and Their Alleviating Strategies - Varadika, Nanda; Zuhriyah, Mukminatus (LPPM Universitas Hasyim Asy'ari Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to analyze students’ writing anxiety at class XI N of MAN 4 Jombang in the academic year of 2024/2025. It focuses on identifying the levels, and the most dominant type of writing anxiety, and the alleviating strategies used by students to reduce their anxiety. The study applied a mixed-methods approach, combining quantitative data from questionnaires using the Second Language Writing Anxiety Inventory (SLWAI) and qualitative data from student interviews. The results showed that the majority of students (67.85%) experienced moderate levels of writing anxiety. Cognitive anxiety was identified as the most dominant type, experienced by 16 out of 28 students (57.14%). Despite these challenges, the interview results showed that the students were able to manage their anxiety through several strategies, such as accepting feedback and mistakes, practicing trough media, asking for help when stuck, practice writing with time management. The findings suggest that while most students are not free from anxiety, they are still able to perform writing tasks with effort and support. These results highlight the importance of both student self-awareness and teacher guidance in managing writing anxiety.